Associated Bacteria Affect Sexual Reproduction by Altering Gene Expression and Metabolic Processes in a Biofilm Inhabiting Diatom - Cirri, Emilio; De Decker, Sam; Bilcke, Gust; Werner, Markus; Osuna-Cruz, Cristina Maria; De Veylder, Lieven; Vandepoele, Klaas; Werz, Oliver; Vyverman, Wim; Pohnert, Georg (Frontiers in Microbiology, 2019)
Diatoms are unicellular algae with a fundamental role in global biogeochemical cycles as major primary producers at the base of aquatic food webs. In recent years, chemical communication between diatoms and associated bacteria has emerged as a key factor in diatom ecology, spurred by conceptual and technological advancements to study the mechanisms underlying these interactions. Here, we use a combination of physiological, transcriptomic and metabolomic approaches to study the influence of naturally co-existing bacteria, Maribacter sp. and Roseovarius sp., on the sexual reproduction of the biofilm inhabiting marine pennate diatom Seminavis robusta. While Maribacter sp. severely reduces the reproductive success of S. robusta cultures, Roseovarius sp. slightly enhances it. Contrary to our expectation, we demonstrate that the effect of the bacteria is not caused by altered cell-cycle regulation prior to the switch to meiosis. Instead, Maribacter sp. exudates cause a reduced production of diproline, the sexual attraction pheromone of S. robusta. Transcriptomic analyses show that this is likely an indirect consequence of altered intracellular metabolic fluxes in the diatom, especially those related to amino acid biosynthesis, oxidative stress response and biosynthesis of defense molecules. This study provides the first insights into the influence of bacteria on diatom sexual reproduction and adds a new dimension to the complexity of a still understudied phenomenon in natural diatom populations.